UI animations with Lottie and After Effects : create, render, and ship stunning After Effects animations natively on mobile with React Native /: create, render, and ship stunning After Effects animations natively on mobile with React Native. (2022) - Martinez, Emilio Rodriguez; Ruiz, Mireia Alegre
No abstract available